'We're all getting the bus Filipino young adults’ perception of their sexual self-concept through their reception on Netflix’s Sex Education. - Lampano, Alyka Mari Santos; Estonilo, Melba S. (Quezon City College of Mass Communication, University of the Philippines, 2023)
The youth's media exposure to sexual content can positively and negatively develop their sexual self-concept, or assessment of their own sexual feelings and actions. While some have argued that such exposure has encouraged positive sexual attitudes among the youth, major studies linking media and sexuality reveal that it has largely produced harmful effects to their sexual self-concept by disseminating negative sexual scripts and inaccurate representations of sex and gender roles.

In the Philippines, the commercial and critical success of the Netflix original series Sex Education has created potential to challenge these assumptions. This qualitative study therefore examined, through the Feminist Media theory and the Sexual Self-Concept theory, how Filipino young adults made sense of their sexual self-concept through their interpretation of Sex Education. I conducted semi-structured, in-depth interviews with 18- to 25-year-old Filipinos who have watched Sex Education.

The findings of this study are of major importance in assessing how media can be a powerful tool in contributing to the sexual awareness of Filipino young adults and addressing the major sexual health problems that they struggle with today, such as unprotected sex, teen pregnancies, and sexually transmitted infections, among others.
Vita.
Thesis
Includes bibliographical references (pages 72-93) and appendices (pages 94-177).
Keywords: Self-concept.; Mass media and sex -- Philippines; Sex in popular culture -- Philippines